Analisis Syair Lagu BE. No. 716 Di Na Mamolus Sandok Ngolu On Pada Kebaktian Minggu Di HKBP Simanungkalit Resort Sipoholon-I - Andrew Fridolin Sihotang; Boho Parulian Pardede; Testi Bazarni Zebua; Monang Asi Sianturi; Roy Josep M. Hutagalung (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
is research aims to clearly understand the poetry structure and meaning of the song Di Na Mamolus Sandok Ngolu On. This research uses a descriptive analysis method with a qualitative approach. The work process carried out is observation, interviews, documentation. Research is carried out by collecting information through field research to obtain results which are processed into original data. The meaning of the lyrics of the song Di Na Mamolus Sandok Ngolu On is first, this also applies to every difficulty and suffering that occurs in our lives. Second, the things we learn through suffering, give us a unique ability to strengthen and comfort people. -people who are experiencing similar difficulties or suffering (2 Corinthians 1:4-5). Third, God provides comfort, not so that we are comfortable, but so that we can provide comfort to others. This song was created by George S. Schuler in 1924, has a 6/8 bar with a tempo of 54 with a basic note of C=do consisting of 24 bars. The song Di Na Mamolus Sandok Ngolu On is an opening song used by Protestants which has a 6/4 meter pattern with the basic note C=do having cross rhymes, namely a, a, b, a. The meaning of the song Di Na Mamolus Sandok Ngolu On is that the things we learn through suffering give us the ability to strengthen and comfort people who are experiencing difficulties or suffering.